Orı́ and neuroscience: a ontextualization of the Yoruba idea of causality in the age of modern science (2018)
This paper examines the submission of neuroscience on freewill within the religious and cultural contexts of the Yoruba in South-western Nigeria. The findings of neuroscience are juxtaposed with the concept of Orı́, with a view to finding how these scientific and religio-cultural lines of determinism can be compatible with the concept of freedom today. The study adopts the hylomorphic theory of Bolaji Idowu, which posits that woman is ara (body) plus ẹ̀mı́ (spirit).